Longitudinal Immune Cell Profiling in Patients With Early Systemic Lupus Erythematosus. Issue 11 (7th October 2022) - Sasaki, Takanori; Bracero, Sabrina; Keegan, Joshua; Chen, Lin; Cao, Ye; Stevens, Emma; Qu, Yujie; Wang, Guoxing; Nguyen, Jennifer; Sparks, Jeffrey A.; Holers, V. Michael; Alves, Stephen E.; et al.
Abstract : Objectives: To investigate the immune cell profiles of patients with systemic lupus erythematosus (SLE), and to identify longitudinal changes in those profiles over time. Methods: We employed mass cytometry with 3 different panels of 38–39 markers (an immunophenotyping panel, a T cell/monocyte panel, and a B cell panel) in cryopreserved peripheral blood mononuclear cells (PBMCs) from 9 patients with early SLE, 15 patients with established SLE, and 14 controls without autoimmune disease. We used machine learning–driven clustering, flow self‐organizing maps, and dimensional reduction with t‐distributed stochastic neighbor embedding to identify unique cell populations in early SLE and established SLE. We used mass cytometry data of PBMCs from 19 patients with early rheumatoid arthritis (RA) and 23 controls to compare levels of specific cell populations in early RA and SLE. For the 9 patients with early SLE, longitudinal mass cytometry analysis was applied to PBMCs at enrollment, 6 months after enrollment, and 1 year after enrollment. Serum samples were also assayed for 65 cytokines using Luminex multiplex assay, and associations between cell types and cytokines/chemokines were assessed. Results: Levels of peripheral helper T cells, follicular helper T (Tfh) cells, and several Ki‐67+ proliferating subsets (ICOS+Ki‐67+ CD8 T cells, Ki‐67+ regulatory T cells, CD19 intermediate Ki‐67 high plasmablasts, and PU.1 high Ki‐67 high monocytes) were increased in patients with early SLE, with more prominent alterations than were seen in patients with early RA. Longitudinal mass cytometry and multiplex serum cytokine assays of samples from patients with early SLE revealed that levels of Tfh cells and CXCL10 had decreased 1 year after enrollment. Levels of CXCL13 were positively correlated with levels of several of the expanded cell populations in early SLE. Conclusion: Two major helper T cell subsets and unique Ki‐67+ proliferating immune cell subsets were expanded in patients in the early phase of SLE, and the immunologic features characteristic of early SLE evolved over time.